Quantitative assessment of the lower limb digital subtraction angiography post successful revascularization using optical flow method (syngo iFlow) - Hamzah, Mohd Helmi (2018)
Background: Digital subtraction angiography (DSA) remains the gold standard in diagnosing complicated peripheral vascular disease and is the only imaging modality capable of visualizing endovascular treatments in all contexts. The purpose of the study is determine the means different of arterial flow time (FT) of DSA on the lower limb circulation pre and post successful revascularization using time density curve (TDC) on syngo iFlow application. Methodology: A total of 45 patients, retrospectively review the pre and post successful revascularization blood flow time using syngo iFlow application. The blood flow time (TTP) of the successful arterial flow is determined by using the application. Mean and SDs were obtained for each measurement, and level of significance for pre and post treatment was studied (P < 0.05). Result: In total of 45 subject was studied (26 male, 19 female, means age 59.3). Stenoses were graded as follows based on the angiographic finding: less than 50% stenosis 2 patients; 50-75% stenosis 37patients; 76-99%, 6 patients. There was a significant difference in means between proximal and distal stenosis for pre treatment (p-value<0.001). The mean difference of pre treatment was -0.84 with mean(SD) for pre and post stenotic segment were 3.94s(0.43) and 4.78s(0.80) respectively. There was also significant mean difference between proximal and distal stenosis for post treatment ( p-value<0.001). The mean difference of post treatment was -0.34 with mean(SD) for pre and post stenotic segment were 3.90s(0.39) and 4.16s(0.52) respectively. Before treatment, means TTP time (time to peak time) between contrast time curve proximal and distal to the treated vessels segment was 3.94s and 4.78s respectively, after treatment was 3.90s and 4.156s respectively. Gain percentage of the improvement time was highest at 62% (n=10), second most 83% (n=6) and 78% (n=6). Using pair t- test analysis, decrease in TTP time was stastistically significant pre and post treatment (p < 0.01). Conclusion: With the significant changes in blood flow parameter pre and post treatment as well as improvement of the gain percentage blood flow time, syngo iFlow application can be the first marker to determine the successful rate of the revascularization technique objectively.